Integração regional fronteiriça entre Argentina e Brasil: atores educacionais, políticas territoriais e governança - Muriel Pinto; Ronaldo Colvero; Domingos Sávio Campos de Azevedo (Confins)
This study analyzes how the governance of border integration between Brazil and Argentina has been taking place based on regional educational networks. As a spatial analysis unit, the Twin Cities of São Borja-Brasil / Santo Tomé-Argentina were chosen. For many decades, border relations have been paradiplomatic in the region, with the formalization of several laws and Integration Committees (CIF’s), relations have become diplomatic. To this end, literature reviews were carried out, and knowledge was tested based on a case study. As partial results, it is noteworthy that the mechanisms of regional integration are supported by Law 26.523 / 2009 (Argentina) and Decree 8636/2016 (Brazil), where the processes are linked to CIF and its sectoral commissions, which act through three strategic processes : survey of demands and referrals; diplomatic and paradiplomatic actions; and decision-making and power bodies (raising awareness among elected actors). In this process, universities assume a central role in regional territorial development.